Intraspecific variation in fruit–frugivore interactions: effects of fruiting neighborhood and consequences for seed dispersal - Guerra, Tadeu J.; Dayrell, Roberta L. C.; Arruda, André J.; Dáttilo, Wesley; Teixido, Alberto L.; Messeder, João V. S.; Silveira, Fernando A. O. (Oecologia, 2017)
The extent of specialization/generalization continuum in fruit–frugivore interactions at the individual level remains poorly explored. Here, we investigated the interactions between the Neotropical treelet Miconia irwinii (Melastomataceae) and its avian seed dispersers in Brazilian campo rupestre. We built an individual-based network to derive plant degree of interaction specialization regarding disperser species. Then, we explored how intraspecific variation in interaction niche breadth relates to fruit availability on individual plants in varying densities of fruiting conspecific neighbors, and how these factors affect the quantity of viable seeds dispersed. We predicted broader interaction niche breadths for individuals with larger fruit crops in denser fruiting neighborhoods. The downscaled network included nine bird species and 15 plants, which varied nearly five-fold in their degree of interaction specialization. We found positive effects of crop size on visitation and fruit removal rates, but not on degree of interaction specialization. Conversely, we found that an increase in the density of conspecific fruiting neighbors both increased visitation rate and reduced plant degree of interaction specialization. We suggest that tracking fruit-rich patches by avian frugivore species is the main driver of density-dependent intraspecific variation in plants’interaction niche breadth. Our study shed some light on the overlooked fitness consequences of intraspecific variation in interaction niches by showing that individuals along the specialization/generalization continuum may have their seed dispersed with similar effectiveness. Our study exemplifies how individual-based networks linking plants to frugivore species that differ in their seed dispersal effectiveness can advance our understanding of intraspecific variation in the outcomes of fruit–frugivore interactions.